(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the effectiveness of applying modern interactive methods in teaching natural sciences. Based on experimental research, the knowledge level, activity, and independent thinking skills of students in the experimental and control groups were compared. The findings demonstrated that the use of interactive methods is an effective tool for enhancing deeper knowledge acquisition, developing practical skills, fostering ecological awareness, and stimulating creative thinking.